2014
DOI: 10.1111/nana.12069
|View full text |Cite
|
Sign up to set email alerts
|

What can and cannot be willed: how politicians talk about national identity and immigrants

Abstract: The ethnic‐civic framework remains widely used in nationalism research. However, in the context of European immigrant integration politics, where almost all ‘nation talk’ is occurring in civic and liberal registers, the framework has a hard time identifying how conceptions of national identity brought forth in political debate differ in their exclusionary potential. This leads some to the conclusion that national identity is losing explanatory power. Building on the insights of Oliver Zimmer, I argue that we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
0
26
0
2
Order By: Relevance
“…The present article also seems to support this latter view. Second, scholars have also challenged the 'liberal-ness' of the civic integrationist 5 turn, suggesting that it still embodies a form of ethno-centric nation-politics aimed at drawing lines of inclusion/exclusion (Mouritsen 2006, Laegaard 2007, Kostakopoulou 2010, Jensen 2014, Larin 2015.…”
Section: Civic Integration Civility and The Civic-ethnic Dividementioning
confidence: 99%
See 2 more Smart Citations
“…The present article also seems to support this latter view. Second, scholars have also challenged the 'liberal-ness' of the civic integrationist 5 turn, suggesting that it still embodies a form of ethno-centric nation-politics aimed at drawing lines of inclusion/exclusion (Mouritsen 2006, Laegaard 2007, Kostakopoulou 2010, Jensen 2014, Larin 2015.…”
Section: Civic Integration Civility and The Civic-ethnic Dividementioning
confidence: 99%
“…This nationalisation of liberal principles (Laegaard 2007) or culturalisation of politics (Mouritsen 2008, Kostakopoulou 2010) reveals for Zimmer (2003) the importance of moving beyond the ethnic/civic distinction. What matters for him is not the actual content of national discourses, but the ways in which this content is mobilized for purposes of inclusion/exclusion (see also Jensen 2014). Thus, for instance, Halikiopoulou et al (2013) have shown how liberal-democratic values figure prominently in the discursive toolkit of radical right parties.…”
Section: Civic Integration Civility and The Civic-ethnic Dividementioning
confidence: 99%
See 1 more Smart Citation
“…Both Borevi (2010) and Joppke (2007) would note that this imposes upon the individual immigrants and releases the state from responsibility for offering means to satisfy this obligation. Jensen (2014) would find this to indicate that individual immigrants are considered able to modify their nationality and that Icelandic society is not so concerned about changing itself to accommodate the newcomers. What are missing from literature investigating the individual-state responsibility, voluntary-fixed identity and voluntarycoerced integration continua are fine-grained investigations of what happens when immigrants comply with state demands.…”
mentioning
confidence: 99%
“…Before, securing immigrants' rights used to be seen to lead to integration into the new society, whereas now, lack of integration is given as a reason for denying people rights. Jensen (2014) analyses portions of the debates in the Norwegian and Danish parliaments concerning methods of integrating immigrants into the two societies. He argues that the differences in approach and rhetoric used by members in the two bodies are influenced by the sense that national identity can or cannot be shaped voluntarily and whether the nation should adapt to incomers.…”
mentioning
confidence: 99%